Convalescent plasma – An insight into a novel treatment of covid-19 ICU patients. (December 2022) - Chowdhry, Mohit; Hussain, Maryam; Singh, Prachi; Lekshmi, Minu; Agrawal, Soma; Kanwar, MS; Chawla, Rajesh; Kantroo, Viny; Bali, Roseleen; Bansal, Avdesh; Chawla, Aakanksha; Modi, Nikhil; et al.
Abstract: Introduction: Various therapies have been tried for Covid disease including the use of antivirals, steroids, monoclonal antibodies and convalescent plasma. Method: The study was conducted on convalescent plasma transfused ICU patients. Part A of the study involves clinical outcomes based on gender, age, comorbidities, blood group, and the average length of stay. Part B investigates clinical outcomes in patients transfused with convalescent plasma before and after the November 2021 guidelines. Part C of the study includes patients in cytokine storm and the efficacy of tocilizumab in these patients.Result: Out of the 326 ICU patients transfused with convalescent plasma the overall mortality was 152 (53.3 %). On comparing blood groups and clinical outcomes, a clinically significant result was found. A clinically significant association was also seen on comparing the clinical outcome of 18–50 years and 61–70 years age group and in female gender patients. The average number of ICU days had a positive impact on the overall patient survival. Out of the patients in 'cytokine storm' (n = 109), on day 20, the survival percentage in the non-Tocilizumab group showed a downward trend throughout. However, in the Tocilizumab group, the survival percentage remained stable throughout till around day 50. Conclusion: Amongst the convalescent plasma transfused ICU patients, females, having blood group B, and an average length of stay of fewer than 20 days had a better chance of survival. The patients given tocilizumab and convalescent plasma had a better chance of survival compared to tocilizumab alone.